Proc. 27th Annual Conference of the International Group for Lean Construction (IGLC) 2019
DOI: 10.24928/2019/0177
|View full text |Cite
|
Sign up to set email alerts
|

Lean, Automation and Modularization in Construction

Abstract: The architecture, engineering and construction (AEC) industry lags behind the manufacturing industry, both in terms of innovation and productivity, mainly due to its heterogeneous, fragmented nature and the uniqueness of its projects. This paper analyzes three effective processes and technologies which are carrying out great benefits to the construction industry: lean construction, automation, and modularization (LAM). The research consists of a systematic literature review and assesses previously published wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…From a distinct perspective, a literature review was developed to assess the interaction between lean construction, automation, and modularization. The result showed that potential research could be carried out to satisfy the three paradigms through robotics, integrated project delivery, and parameterization (Brissi and Debs, 2020). The last two papers in this review are unique in nature.…”
Section: Othersmentioning
confidence: 90%
“…From a distinct perspective, a literature review was developed to assess the interaction between lean construction, automation, and modularization. The result showed that potential research could be carried out to satisfy the three paradigms through robotics, integrated project delivery, and parameterization (Brissi and Debs, 2020). The last two papers in this review are unique in nature.…”
Section: Othersmentioning
confidence: 90%